Candida Infections in Intensive Care Unit Patients: How to Diagnose? - BİLGİLİ, BELİZ (AVES, 2020)
Candida infection is a serious problem associated with increased morbidity and mortality in intensive care unit (ICU). Multiple risk factors and severe diseases make patients vulnerable to fungal infections in ICUs. Diagnosis of Candida infections should be established rapidly in order to initiate the efficient treatment early. Diagnosis of Candida infections is a very challenging process for clinicians due to comorbidities and complex clinical conditions in the critically ill patients. Growth of the agent in blood, sterile body fluid and tissue cultures or histopathological diagnosis are the main methods for the diagnosis. The biomarkers for fungal agents and various risk factors of the patient are also used for diagnostic purposes with clinical evaluation.
Keywords: Candidiasis; critical illness; biomarkers; CRITICALLY-ILL PATIENTS; BETA-D-GLUCAN; INVASIVE CANDIDIASIS; COLONIZATION INDEX; RISK-FACTORS; BLOOD; ASSAY; SUBSEQUENT; SCORE; MANAGEMENT